THE PREVALENCE OF INDIAN COMMON KRAIT ENVENOMATION AND ITS CLINICAL COMPLICATIONS AMONG THE RURAL POPULATIONS OF INDIA - Ramaswamy, Malathi; Duraikannu, Sivakumar; Solaimuthu, Chandrasekar (Journal of Drug Delivery and Therapeutics, 2018)
Snake envenomations have been a serious yet often overlooked public health threat especially in tropical and subtropical countries, including Southeast Asia. The medically important venomous land snakes in Southeast Asia include snakes from the Elapidae and Crotalidae families. Among the elapids, there are only 12 species that are considered of medical importance, represented by the kraits (Bungarus caeruleus, B. candidus, B. fasciatus, B. flaviceps and B. multicinctus). The incidence of snakebite is high in India. Apart from mortality, the morbidity is due to various complications. The common krait (Bungarus caeruleus) is the most toxic snake found commonly in the plains of throughout the India and the number of snakebites in the rural areas of India was recorded by this snake. The present article highlights the prevalence and the clinical complications of Indian common krait envenomation among the rural populations of India. Keywords: snake bite, common krait, clinical complications and rural area